ISO 9001:2015 QUALITY MANAGEMENT SYSTEM DESIGN IN SMES - Puti Renosori; Hirawati Oemar; Aripah Sita Apriani (Journal of Industrial Engineering Management, 2023)
A proper quality management system is essential for managing company activities to meet customer requirements. Management of quality necessitates an organizational structure, roles, processes, and resources. In this situation, the analyzed small and medium enterprises (SMEs) have limited human resources and non-standard procedures; So, in order to improve their quality management system, companies need both internal and external support. The objective of this design is to create and document ISO 9001:2015 quality management standards in order to improve consumer satisfaction. This research employs gap analysis and risk analysis as its methods. The results obtained from the gap analysis calculation in clause 5 receive the highest score of 71%, while the other clauses receive less than 50%, stating that a quality management system based on ISO 9001:2015 has not been implemented. Proposals in the design of a quality management system in the form of creating documents based on discrepancies and voids that have been identified.